Kesehatan Ala Hipnoterapi Islam - Ibrahim Ibrahim (JURNAL ILMIAH SYI'AR, 2018)
The term hypnotherapy refers to the word "Hypno" in Greek meaning sleep. Indeed, hypnotherapy healing therapy begins with conditioning the patient in a phase of relaxation (like people fall asleep) before core therapy is carried out. Hypnotherapy works on the human subconscious (alpha state). For the unconscious soul to rise, the patient must enter a state of relaxation, or rest his conscious soul. In this condition, subconscious recording such as perceived health problems will be known. Subconscious records that are wrong or wrong will be updated by giving positive suggestions by the therapist through hypnotherapy. This suggestion is given continuously until the unconscious recording state is reached which is wrongly disappeared and replaced by suggestion positive. The success rate of positive suggestions in patients is certainly different in each person. Depending on the severity of the disease, and the willingness to recover from the patient's self. In Hypnotherapy the healing process can be done in one or several therapies. All depends on the interference experienced. In hypnotherapy, the therapist only acts as a facilitator. Patients who must be proactive and have a strong will to recover. As active subjects, patients must also be cooperative while understanding the intent and purpose of hypnotherapy. There must be an agreement between the patient and the therapist, because the patient is the one who really knows what he is suffering from.